Training the trainers: finding new educational opportunities in the virtual world - Baessler, Franziska; Sartorius, Norman; Javed, Afzal; Tasman, Allan; Coskun, Bulent; Frydecka, Dorota; Kazakova, Olga; Sampogna, Gaia; Zhabenko, Olena; Koelkebeck, Katja; Hepdurgun, Cenan; Zafar, Ali; et al. (Asia-Pacific psychiatry, 2021)
The COVID-19 pandemic has disrupted scientific gatherings and conferences, opening up opportunities for virtual learning platforms. Realizing the potential of online academic exchanges, the World Psychiatric Association (WPA) also developed virtual avenues and information systems for capacity building of mental health professionals across the world. Among its first such initiatives, the WPA organized a virtual Train the Trainers workshop, where 123 psychiatrists, psychiatric trainees, and educators from 45 countries participated. The innovative and interactive workshop allowed participants to get to know each other, exchange educational and professional experiences, and ask questions or receive advice from experts. Keynote speakers, including WPA President Prof. Afzal Javed and Prof. Norman Sartorius, stressed upon the importance of finding innovative solutions in psychiatry training and the need to improve teaching and training in the field of psychiatry, especially in the provision of leadership and communication skills. Online training methods can provide easy access to academics and students while reducing the organizational and logistical costs. They have the potential to improve educational equality and allow the voice of the underprivileged scientists to be heard across the globe. The devastating impact on access to mental health services during COVID-19 underscores the urgent need for online training, particularly in countries where the ratio of psychiatrists to patients is inadequate and doctors concentrate more on treatment than on research and education. Virtual educational interventions could prove incredibly useful in the future just as they are being successfully utilized in local and regional contexts during the pandemic.